REPRESENTASI IDENTITAS DIGITAL PELARI KALCER PADA AKUN INSTAGRAM KOMUNITAS @UNIONSUBCULTURE - Wicaksono, Imam; Augustin Mustika Chairil (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to identify and describe the process of digital identity representation of "pelari kalcer" (culture runners) through content uploaded on the Instagram account @unionsubculture. The culture runner phenomenon indicates a shift in the meaning of running, evolving from a mere physical fitness routine into a space for constructing social identity and urban lifestyle. Utilizing a qualitative descriptive method, this research applies Charles Sanders Peirce’s Semiotics (Sign, Object, Interpretant). The data corpus consists of 15 visual contents (photos and videos) published between March 2025 and March 2026. The analysis reveals that @unionsubculture consistently portrays visual patterns adapting the "New York Urban Style" and 1980-1990s underground street culture. This is evident in three main dimensions: (1) the use of dark-colored streetwear outfits and non-athletic attributes, (2) street photography aesthetics (slow shutter, motion blur, flash) capturing night urban landscapes, and (3) graphic designs heavily influenced by grunge, DIY collages, and aggressive typography akin to underground gig posters. In conclusion, the community consciously practices bricolage reassembling punk/skate subculture elements to break the formal image of conventional running and establish their digital existence as free-spirited, independent, and rebellious runners.